Human Development On The Educational Dimension in East Kutai Regency - Siti Amalia; Diana Lestari; Siti Maria (Technium Social Sciences Journal, 2024)
The Human Development Index (HDI) is a key metric for measuring achievement in improving human well-being. Various factors, such as economic growth and household expenditure, can have an impact on education’s human development dimension. The purpose of this study is to examine the impact of economic expansion on household expenditure and human development in terms of schooling. The data analysis technique employs Multiple Regression with SmartPLS SEM (Partial Least Square - Structural Equation Modeling) software. According to the study’s findings, economic growth has a significant effect on household spending, but not on human development in the educational dimension, household spending has a significant impact on economic development in the educational dimension, and household spending can mediate the influence of economic growth on human development in the educational dimension in East Kutai. Finally, it is vital to boost economic growth based on the agricultural sector, which can improve the welfare of the community, hence increasing human development in the educational dimension in East Kutai Regency.